No effect of teriparatide on migration in total knee replacement: A randomized controlled trial involving 50 patients. (4th May 2017) - Ledin, Håkan; Good, Lars; Johansson, Torsten; Aspenberg, Per
Abstract : Background and purpose — Aseptic loosening is a main cause of late revision in total knee replacement (TKR). Teriparatide, a recombinant parathyroid hormone (PTH), stimulates osteoblasts and has been suggested to improve cancellous bone healing in humans. This might also be relevant for prosthesis fixation. We used radiostereometric analysis (RSA) to investigate whether teriparatide influences prosthesis fixation. Early migration as measured by RSA can predict future loosening. Patients and methods — In a randomized controlled trial with blind evaluation, 50 patients with osteoarthritis of the knee were allocated to a teriparatide treatment group (Forsteo, 20 μg daily for 2 months postoperatively) or to an untreated control group. RSA was performed postoperatively and at 6 months, 12 months, and 24 months. The primary effect variable was maximal total point motion (MTPM) from 12 to 24 months. Results — Median maximal total point motion from 12 to 24 months was similar in the 2 groups (teriparatide: 0.14 mm, 10% and 90% percentiles: 0.08 and 0.24; control: 0.13 mm, 10% and 90% percentiles: 0.09 and 0.21). [Authors: this is perhaps better than using "10th" and "90th", which looks ugly in print./language editor] The 95% confidence interval for the difference between group means was −0.03 to 0.04 mm, indicating that no difference occurred. Interpretation — We found no effect of teriparatide on migration in total knee replacement. Other trials using the same dosing have suggested a positive effect of teriparatide on human cancellous fracture healing. Thus, the lack of effect on migration may have been due to something other than the dose. In a similar study in this issue of Acta Orthopaedica, we found that migration could be reduced with denosumab (Ledin et al. 2017 ). The difference in response between the anabolic substance teriparatide and the antiresorptive denosumab suggests that resorption has a more important role during the postoperative course than any deficit in bone formation.